1980
DOI: 10.1017/s0022215100089763
|View full text |Cite
|
Sign up to set email alerts
|

Healing and hearing in uncomplicated myringoplasty

Abstract: In closing an uncomplicated central drum defect the technique known as an ‘underlay’is widely used. This method has certain advantages and yields good results as far as both healing and hearing are concerned. In an attempt further to improve reults the authors give an account of a series of myringoplasties and specifically discuss the unsuccessful cases. By a slight alteration in the operative technique used in the series presented, the authors believe that some failures can be avoided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1982
1982
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…3. Mendel and Kuylenstierna (1980) noted that graft failures occurred more frequently in front of the handle of the malleus and postero-inferiorly. They did not use gelfoam.…”
Section: Fig 4 Grafting a Large Perforationmentioning
confidence: 99%
“…3. Mendel and Kuylenstierna (1980) noted that graft failures occurred more frequently in front of the handle of the malleus and postero-inferiorly. They did not use gelfoam.…”
Section: Fig 4 Grafting a Large Perforationmentioning
confidence: 99%
“…Although there are strong advocates of both overlay and underlay tympanoplasty, the former has become less popular because it is time consuming; requires considerable expertise to master; and carries a greater risk of blunting, graft lateralization, and trapped epithelium in the middle ear. [1][2][3][4] Laying the graft under the drum remnant and over the malleus has been proposed to circumvent these difficulties. 6 Unfortunately this does not prevent the trap- ping of epithelium under the graft even in expert hands.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, large anterior and total TM perforations leave little or no drum remnant under which the underlay graft can be securely tucked, making them more susceptible to graft migration and failure. [1][2][3][4] A recent retrospective study of underlay grafting reported a meager 67% success with the repair of anterior or total perforations, compared with 90% success with posterior and inferior perforations, underscoring the difficulties of anterior perforations. 5 Not unexpectedly, large anterior and total perforations are more daunting to the occasional otologist.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation